Balanced Macromolecular Biosynthesis in “Protoplasts” of Streptococcus faecalis - Roth, George S. (1971)
Osmotically fragile forms of Streptococcus faecalis 9790 were grown in 0.5 m sucrose- or 0.5 m NH(4)Cl-stabilized medium. The “protoplast” cultures exhibit an average growth rate constant of 0.66 to 0.94 mass doublings/hr. In a variety of experiments, turbidity and the net content of protein, ribonucleic acid (RNA) and deoxyribonucleic acid increase at the same rate, indicating balanced macromolecular biosynthesis. A total of two to three mass doublings was obtained, with no evidence of cell division. After osmotic shock, “protoplast” cultures released 93 to 94% of their RNA content in a form not sedimentable at 12,800 × g for 15 min, in contrast to streptococci, which released 7% of their RNA content after the same treatment.